Pendampingan Berhitung Pada Anak Sekolah Dasar Menggunakan Media “Papan Pintar Berhitung” - Siti Dian Mulyanti; Siti Nurhasanah; Dede Imtihanudin; Badri Munawar; Linda Linda (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The purpose of this mentoring activity is to teach the concept of counting to elementary school media. This training activity consisted of 3 stages, namely the first stage of observation, the second stage students in the base village of the base village by using the "smart counting board" learning of socialization and the third stage of mentoring. As for this mentoring activity, the subjects were elementary school students in the base village of the base village. The method used in this community service is mentoring carried out routinely. The result of this assistance is that children can understand the concept of counting by using media and to foster children's motivation to learn mathematics.